Optimal tumour control for early-stage non-small-cell lung cancer: A radiobiological modelling perspective. (October 2019) - Alaswad, Mohammed; Kleefeld, Christoph; Foley, Mark
Highlights: Developed a mechanistic TCP model to predict local tumour control for NSCLC. The TCP model trained clinical outcomes for 3D-CRT, CHART and SABR. The model is useful for local tumour control prediction in high dose radiotherapy. The impact of clonogenic cell density variations on tumour control was assessed. 60% of the dose was sufficient to maintain a flat TCP a cross the tumour volume. Abstract: A fully heterogeneous population tumour control probability (TCP) model, based on the linear-quadratic (LQ) cell survival concept combined with the Poisson statistic, was established to predict local tumour control after one, two and three years. This TCP model was created using data from 16 publications that reported on early-stage non–small-cell lung cancer (NSCLC) treated using either three-dimensional conformal radiation therapy (3D-CRT), continuous hyperfractionated accelerated radiotherapy (CHART) or stereotactic ablative body radiotherapy (SABR). The TCP model was fitted to the clinical outcome data using optimised radiosensitivity values produced by the Nelder-Mead simplex algorithm. The statistical analysis resulted in R 2 values of 0.96, 0.96 and 0.97 and wRMSE values of 3.9%, 5.2% and 5.9% for one-, two- and three-year local tumour control rates, respectively. The TCP models for one, two and three years were internally validated using a bootstrap resampling approach. The mean R 2 and 95% CI for the bootstrap samples were 0.98 (0.93–0.99), 0.98 (0.95–0.99) and 0.98 (0.96–0.99) for the one-, two- and three-year local tumour control rates, respectively. Variations in the TCP with clonogenic density were then further investigated by introducing a new mathematical model to vary the clonogenic cell and radiation dose distribution across the treated volume. Based on the above model, it was estimated that 60% of the dose was sufficient to maintain the TCP after two years for the areas with lower clonogenic cell density. If externally validated, this lower-dose treatment plan could have beneficial effects on the surrounding healthy tissue without negatively affecting tumour control.